Fortifikasi Perekat Lateks Karet Alam-Stirena dengan Isosianat: Karakteristik dan Aplikasinya pada Kayu Lapis (Fortification of Natural Rubber Lateks-Styrene with Isocyanate: Characteristics and its Application for Plywood Adhesive) - Widya Fatriasari; Surdiding Ruhendi (Masyarakat Peneliti Kayu Indonesia, 2010)
This study was to evaluate the blending composition effects of natural rubber lateks-styrena (NRL-St)/isocyanate adhesive on their properties and sengon plywood quality. The blending mixture consists of 100/0, 90/10, 80/20, 70/30 and 0/100. Physico-chemical properties of these adhesives in therms of solid content (gravimetric method), pH (pH indicator paper), viscosity (Viscometer Brookfield), and contact angle (Motic software) were characterized. The bond strength (SNI 01-2704-1992) and formaldehyde emission (WKI bottle method) of plywood were also determined. Isocyanate fortification increased the solid content and viscosity of adhesive mixture, while pH was vice versa. The contact angle of adhesive mixture was about 450.Isocyanate fortification onto NRL-St improved plywood bond strength and significant improvement was happened on the composition of 80/20. Plywood hot pressing for 5 minutes increased the bond strength until isocyanate fortification 20%, while 10 minutes hot pressing also improved the bond strength on all of the composition adhesive. Only adhesive mixture of 70/30 that gave the lowest formaldehyde emission and fulfiled E1 standard (<0.1 ppm). Generally,the increasing of hot pressing time tended to decrease formaldehyde emmision of plywood. Bond strength of plywood fulfill SNI standard and E1 standard was isocyanate fortification of 30%.